2010
DOI: 10.1021/la9048743
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Live Cells with Nanocarbon Substrates

Abstract: Nanocarbon materials, including single-walled carbon nanotubes (SWCNTs) and graphene, promise various novel biomedical applications (e.g., nanoelectronic biosensing). In this Letter, we study the ability of SWCNT networks and reduced graphene oxide (rGO) films in interfacing several types of cells, such as neuroendocrine PC12 cells, oligodendroglia cells, and osteoblasts. It was found that rGO is biocompatible with all these cell types, whereas the SWCNT network is inhibitory to the proliferation, viability, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
220
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(226 citation statements)
references
References 28 publications
6
220
0
Order By: Relevance
“…In a similar way, Agarwal et al 87 recently demonstrated the biocompatibility of reduced GOs with proteins and further used them after protein functionalization to create biosensors for detecting various metals in real time with high sensitivity. 81 These reports already confirm the potential of graphene for sensing in aqueous electrolytes, however, detailed understandings of the graphene/ electrolyte interface and the effect of the electrolyte on the electronic transport in graphene are still lacking.…”
Section: Grapheneàdetection In Liquid Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, Agarwal et al 87 recently demonstrated the biocompatibility of reduced GOs with proteins and further used them after protein functionalization to create biosensors for detecting various metals in real time with high sensitivity. 81 These reports already confirm the potential of graphene for sensing in aqueous electrolytes, however, detailed understandings of the graphene/ electrolyte interface and the effect of the electrolyte on the electronic transport in graphene are still lacking.…”
Section: Grapheneàdetection In Liquid Environmentmentioning
confidence: 99%
“…This indicates that they were measuring a signal that was averaged from different points across the outer membrane of the beating cells. In another recent work, Agarwal et al 87 demonstrated the biocompatibility of reduced GOs with live cells, such as neuroendocrine PC12 cells, and further used them to create biosensors for detecting the dynamic secretion of the hormonal catecholamine molecules from living cells. 80 Pursuing the development of a graphene-based technology that can detect action potentials from electrically active cells, Hess et al 84 recently reported using arrays of CVD-grown graphene FETs for the extracellular detection of action potentials from electrogenic cells (Figures 7c and d).…”
Section: Fet Biosensors S Liu and X Guomentioning
confidence: 99%
“…Additionally, cytotoxicities of graphene and graphene-based materials have also been tested in mice cell lines and have been shown to have negligible toxicity at low concentrations. 239,240 Interestingly, similar low concentrations have been linked to cytotoxic effects when using other carbon-based materials like CNTs. [240][241][242] The negligible toxicity of graphene towards cell lines has resulted in various research groups using graphene-based materials as scaffolds for cell growth.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 97%
“…250,251 Various in vitro toxicity studies have been conducted to determine the toxicity of graphene towards cancer [234][235][236][237][238] and human cell lines. 229,239 The cytotoxicity towards the cancer cell lines A549 was shown to depend largely on the cell culture medium components. 234,235 In particular it was noted that fetal bovine serum played a very important role, as it seems to coat the graphene sheets making them less toxic towards cell lines.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%
See 1 more Smart Citation